Peroxidase Activity and Isoperoxidase Pattern in Tobacco Leaves Infected with Tobacco Necrosis Virus and Otber Viruses Inducing Necrotic and Non-Necrotic Alterations - Montalbini, P.; Buonaurio, R.; Umesh Kumar, N. N.
The level of peroxidase activity was greatly enhanced in tobacco leaves infected by tobacco necrosis virus (TNV)and other viruses which induce neerotie symptoms (TMV, ToM V and PVY^). The intensity was related to the age of the leaves infected: absent or negligible in mature leaves and very pronounced in young growing infected leaves. On the eontrary, changes in peroxidase activity were negligible when the infection was provoked by viruses which do not produce necrotic reactions (TMV and PVY°). Analysis of the peroxidase isoenzynie pattern in tobacco leaves infected by TNV and other necrosis-inducing viruses revealed in all cases, a slight increase in anionic (pi 3.5-3.7)and a considerable increase in moderately anionic isoenzymes, particularly the pi 4.6 isoenzyme which in TNV and PVY'^-infected leaves reached levels up to 21 and 72 times the healthy control values. A considerable increase in the cationic (pi 9.3-8.8)isoenzymes and the appearance of one moderately cationic isoenzyme (pi 8.2)was also detected. In leaf extracts from virus-infected tobacco leaves with nonnecrotic response, no, or negligible alterations on the isoenzyme pattern were detected. However, infection by a fungal parasite (Erisyphc eiehoracearwn), which established a fully compatible, non-neerotic, interaction with tobacco leaves, like the necrosis-inducing viruses, changed the isoperoxidase pattern. The data suggest the necrotic alterations and associated changes in the peroxidase activity and isoperoxidase pattern in virus-infected leaves are not clearly reUited.